SANKSI HUKUM TERHADAP PELAKU GAME ONLINE DITINJAU DARI HUKUM ISLAM DAN HUKUM NASIONAL - Gunawan, Hendra; Yanti, Sri Afrida (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This paper aims to analyze legal sanctions for online game players, especially domino or scatter online games. Every act of gambling is prohibited by laws and regulations, as stipulated in Article 303 of the Criminal Code. The reasons for playing games are very diverse, some are to fill the void of time but can be haram (not allowed), if there is an element of betting (gambling). This research is a normative-juridical legal research, so to answer this question the author digs from literature and electronic media that discusses the intricacies of domino or scatter games, then analyzes from the point of view of Islamic law, about the elements why legal sanski does not run officially. The results of this study show that legal sanctions for online gambling players can be sentenced to imprisonment for 10 years (Article 30 of the Criminal Code). While Article 303 BIS regulates unlicensed gambling.